(untitled) (Jurnal Huma Betang Demokrasi, 2021)
This research article analyzes the comparison of the procedures for resolving disputes over the results of the 2020 regional head elections with those used previously and their application in the framework of realizing the regional head elections with integrity. By using a normative juridical research approach, the results of the study conclude that first, the procedure for resolving disputes over the results of the 2020 regional head elections has differences from those used previously. The differences in question include arrangements regarding the terms of the object of dispute, preliminary examination, trial examination, as well as the position of Provincial Bawaslu and Regency/City Bawaslu as information providers. Second, there are still inconsistencies in the application of the procedure for resolving disputes over the results of the 2020 regional head elections by the Constitutional Court, particularly with regard to (1) the judicial dispute over the results of the election as a procedure provided for examining and deciding on election results which includes a series of "processes" for determining vote acquisition; (2) the provisions of stages and schedules; and (3) the scope of the trial examination and further trial examination.